Sistem Informasi Penjualan Sparepart Motor pada Toko Ketapang Motor Margasari - Wati, Fanny Fatma; Anggraini, Recha Abriana; Hidayati, Nadiyah; Maulidah, Mawadatul (LPPM UBSI Kampus Kota Tegal, 2025)
Developments in the increasingly rapid technological era have resulted in business people encouraging their companies to run more effectively along with the times. This is done in order to maximize profits. One technology that is often looked at is information system technology in the form of websites. The Ketapang Motor Shop, which is a motorbike spare parts and accessories trading business, has several problems including the sales report section, stock reports that are not recorded and not filed every month so that existing data is often lost. In sales transactions, payments are still made using notes so that the calculation and inventory of goods is not yet effective. Therefore, a website-based sales information system was created using the waterfall system development method to overcome this problem. The website was created using several programming languages, namely HTML, PHP, CSS, Bootstrap, and Javascript with MySQL as the data storage database. The existence of this website will help companies, especially in the recording process at the cashier so that the quality of the information presented is more accurate.